Deuterium supersaturation in low-energy plasma-loaded tungsten surfaces. (11th November 2016) - Gao, L.; Jacob, W.; von Toussaint, U.; Manhard, A.; Balden, M.; Schmid, K.; Schwarz-Selinger, T.
Abstract: Fundamental understanding of hydrogen–metal interactions is challenging due to a lack of knowledge on defect production and/or evolution upon hydrogen ingression, especially for metals undergoing hydrogen irradiation with ion energy below the displacement thresholds reported in literature. Here, applying a novel low-energy argon-sputter depth profiling method with significantly improved depth resolution for tungsten (W) surfaces exposed to deuterium (D) plasma at 300 K, we show the existence of a 10 nm thick D-supersaturated surface layer (DSSL) with an unexpectedly high D concentration of ~10 at.% after irradiation with ion energy of 215 eV. Electron back-scatter diffraction reveals that the W lattice within this DSSL is highly distorted, thus strongly blurring the Kikuchi pattern. We explain this strong damage by the synergistic interaction of energetic D ions and solute D atoms with the W lattice. Solute D atoms prevent the recombination of vacancies with interstitial W atoms, which are produced by collisions of energetic D ions with W lattice atoms (Frenkel pairs). This proposed damaging mechanism could also be active on other hydrogen-irradiated metal surfaces. The present work provides deep insight into hydrogen-induced lattice distortion at plasma–metal interfaces and sheds light on its modelling work.